Birthing and Parenting a Premature Infant in a Cultural Context - Brooks, Jada L. (Qual Health Res, 2015)
The purpose of this longitudinal qualitative descriptive study was to explore American Indian (AI) mothers’ perceptions of parenting their premature infants over their first year of life in the context of their culture, including the birth and hospitalization experience. A convenience sample of 17 AI mothers and their premature infants were recruited from either a neonatal intensive care unit (NICU) or pediatric clinic in the southeast. Semistructured interviews were conducted at two time points. Through content analytic methods, three broad categories were revealed: descriptions of having a premature infant in the NICU, descriptions of parenting a premature infant, and the influence of Lumbee culture on parenting a premature infant. Certain aspects of AI culture appear to be important in having a premature infant in the NICU and in parenting a premature infant. We recommend that healthcare providers deliver culturally appropriate care that fully supports AI mothers and their premature infants.